Degradation Behaviors of Adhesion Strength between Epoxy Resin and Copper Under Aging at High Temperature. (2017) - Tonozuka, Yu; Shohji, Ikuo; Koyama, Shinji; Hokazono, Hiroaki
Abstract: The aim of this study is to investigate degradation behaviors of the adhesion strength of the resin (bisphenol F-type epoxy resin)/metal interface under aging at high temperature. The adhesion strength of the Cu joint with the resin was investigated by the tensile test. Fracture surfaces were analyzed by Fourier transform infrared spectroscopy (FT-IR) to investigate the degradation mechanism of the adhesion strength of the resin/Cu interface. The tensile strength of the resin itself was also investigated. Although the tensile strength of the resin was 83.3 MPa before aging, it fell to approximately half after aging at 175 o C for 100 h and gradually decreased with aging until 1000 h. The degradation of the resin was caused by thermal decomposition and oxidation of it. The tensile strength of the Cu joint with the resin is 8.9 MPa before aging and it gradually decreased with aging at 175 o C and fell to half or less after aging for 1000 h. The strength of the Cu joint with the resin was lower than the tensile strength of the resin. The degradation of the adhesion strength was caused by cutting C-C bonds by thermal decomposition of the resin. The cut C-C bonds reacted with H2 O in the interface and thus the number of hydrogen bonding between hydroxy group and the Cu oxide film decreased. The reduction of hydrogen bonding caused to decrease the strength of the resin/Cu interface.